2013
DOI: 10.1007/s12288-013-0249-0
|View full text |Cite
|
Sign up to set email alerts
|

Successful Aortic Valve Replacement Surgery in a Patient with Severe Haemophilia a with Low Titre Inhibitor

Abstract: In spite of the modern day innovations, managing severe Haemophilia patients with inhibitors continues to be a challenge. The management of patients with severe haemophilia with inhibitors who are undergoing major surgeries like open heart surgery is technically demanding, fraught with peri-operative complications and needs a multidisciplinary approach. We describe a young man with severe haemophilia with low titre inhibitors who underwent a successful open heart surgery and aortic valve replacement, supported… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Surprisingly, there was a wide etiological spectrum, although many authors reported only the implantation of the prosthesis or the valve repair and not the pre-existing valvular lesions. The youngest patients, aged between 23 and 27, underwent surgery for rheumatic valvular disease [ 4 , 12 , 13 ]. Three cases of infective endocarditis (IE) were reported, two affecting the aortic valve (AV) [ 6 , 14 ] and one the mitral valve (MV) [ 15 ].…”
Section: Etiological Spectrum Of Valvular Lesionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Surprisingly, there was a wide etiological spectrum, although many authors reported only the implantation of the prosthesis or the valve repair and not the pre-existing valvular lesions. The youngest patients, aged between 23 and 27, underwent surgery for rheumatic valvular disease [ 4 , 12 , 13 ]. Three cases of infective endocarditis (IE) were reported, two affecting the aortic valve (AV) [ 6 , 14 ] and one the mitral valve (MV) [ 15 ].…”
Section: Etiological Spectrum Of Valvular Lesionsmentioning
confidence: 99%
“…There were a few exceptions. A 47-year-old patient with severe HA [ 18 ] and a 23-year-old patient with severe HA and inhibitors [ 12 ] received aortic bioprostheses. A Bentall operation with a biologic composite graft was performed on a 43-year-old patient with severe HA [ 22 ].…”
Section: Prosthetic Cardiac Devicesmentioning
confidence: 99%
See 2 more Smart Citations